Antiviral drugs for coronavirus disease 2019 (COVID-19): a systematic review with network meta-analysis. Issue 2 (1st February 2022) - Okoli, George N.; Rabbani, Rasheda; Al-Juboori, Amenah; Copstein, Leslie; Askin, Nicole; Abou-Setta, Ahmed M.
ABSTRACT: Background: To better inform clinical practice, we summarized the findings from randomized controlled trials (RCTs) of antivirals for COVID-19. Methods: We systematically searched for literature up to September 2020, and included English-language publications of RCTs among hospitalized COVID-19 patients. We conducted network meta-analysis combining results of both the direct and indirect comparisons of interventions. The efficacy outcomes were clinical progression, all-cause mortality, and viral clearance, and safety outcomes were diarrhea, nausea, and vomiting. We generated treatment rankings (best to worst) and summarized rank probabilities using rankogram. Results: We included 15 RCTs (14, 418 patients) from 7, 237 retrieved citations. There was no evidence for efficacy of the assessed antivirals compared with placebo/no treatment or with another antiviral for all efficacy outcomes. Lopinavir (400 mg)/ritonavir (100 mg) significantly increased diarrhea, nausea, and vomiting compared with placebo/no treatment and other antivirals, and was ranked worst for these outcomes, while triazavirin (250 mg), baloxavir marboxil (80 mg), and remdesivir (100 mg – 10 days) ranked best, respectively. Conclusions and relevance: The available evidence does not support the use of any antiviral drugs for COVID-19. Cautious interpretations of the findings are, however, advised considering the paucity of the evidence. More RCTs are needed for a stronger evidence base.